1984
DOI: 10.1111/j.1469-7610.1984.tb00149.x
|View full text |Cite
|
Sign up to set email alerts
|

The Self‐concept of Physically Handicapped Children and Their Non‐handicapped Siblings: An Empirical Investigation

Abstract: Following a brief review of studies devoted specifically to the self-concept of the child with a physical handicap and the non-handicapped sibling, 20 pre-adolescent physically handicapped children attending normal schools and their siblings nearest in age were administered the Piers-Harris Self-Concept Scale for Children. Their responses were then compared with those of 13 physically handicapped children attending special schools and their siblings, and with 18 non-handicapped children and their siblings. It … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
59
1
1

Year Published

1988
1988
2006
2006

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 80 publications
(62 citation statements)
references
References 13 publications
1
59
1
1
Order By: Relevance
“…Four studies [51][52][53][54] included similar numbers of males and females, whereas two studies 49,50 did not provide information on the sex of their participants. A variety of types of CP (e.g.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Four studies [51][52][53][54] included similar numbers of males and females, whereas two studies 49,50 did not provide information on the sex of their participants. A variety of types of CP (e.g.…”
Section: Resultsmentioning
confidence: 99%
“…spastic diplegia, hemiplegia, quadriplegia, and athetoid) were represented in the three studies that described the type of CP of the participants. 49,51,54 Two studies 51,54 indicated the severity of CP in their participants with most participants having disabilities that were classified as mild or moderate in severity.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations